Implementasi Perjanjian Bagi Hasil dalam Pengelolaan Terasering Ceking ( Studi Kasus Di Desa Kedisan, Kecamatan Tegallalang ) - Gusti Ngurah Oka Pramana; I Ketut Kasta Arya Wijaya; Luh Putu Suryani (Warmadewa Press, 2022)
Tourism is a complex sector since it has a multi-dimensional nature physically, politically, socio-culturally and economically. Development in the tourism sector will have an impact on increasing regional income. For example, the Gianyar area has many tourism destinations, including the Ceking Terrace Tourism Object. This tourism destination has a view of the terraces located in the middle of the Kedisan Traditional Village, Tegallalang sub-district. This study examines the arrangement of profit sharing and the implementation of profit sharing agreements in the management of the Ceking Terrace tourism object. The research method used is empirical legal research. The results of the study indicate that the legal arrangement regarding profit sharing for the management of Terasing Ceking tourism objects is contained in the provisions of the Gianyar Regency Regional Regulation No. 10 of 2013. This regulates the determination of traditional villages and traditional institutions to have the right to share the profits of the Ceking Terrace tourism object. Then, the profit sharing agreement includes the rights and obligations of the parties in managing the Ceking Terrace tourism object, namely the Management of the Ceking Terrace Tourism Object has a right as a guarantee from the agreed contract. The management also has obligations that must be carried out so that management runs well, land owners are also entitled to compensation for the rice fields that are used as views with the obligation to maintain the beauty of their fields according to the agreement. be subject to sanctions in the form of compensation payments.